Martin Scorsese – Shusako Endo: Silence (2016): How Silence speaks (The Macau Ricci Institute Journal, 2023)
Both the novel and the movie “Silence” feature cowards as “Anti-Heroes” as they reflect the amazement of the writer Shusako Endo and the movie director Martin Scorsese regarding how Jesus calls men and women to follow him who seem completely unfit to face all the hardships and challenges of sharing His cross. Silence emerges as a key driver of a profound transformation from the devastating experience of anxiety, abandonment, torture and failure towards the self-abandonment of the Risen Lord, who calls cowards to step into his life journey.